Effect of Age and Socio Economic Status on the Quality of Life of Patients with Cervical Cancer Undertaking Chemotherapy at Dr. Moewardi Hospital Surakarta - Hidayah Nur Fadhilla; Ambar Mudigdo; Setyo Sri Rahardjo (Masters Program in Public Health, 2017)
Background: Cervical cancer is a type of cancer affecting women with high incidence and mortality in the world. Patient with cervical cancer have to undertake prolonged sequential treatment and therefore may experience physical, physicological and social changes, which may affect their quality of life. This study aimed to examine effect of age and socio economic status on the quality of life of patients with cervical cancer undertaking chemotherapy at Dr. Moewardi hospital Surakarta.Subjects and Method: This was an analytic observational study with cross-sectional design. This study was conducted at Dr. Moewardi Hospital, Surakarta, from February to March 2017. A sample of 100 patients was selected by fixed disease sampling. The dependent variable was quality of life. The independent variables were age, education and family income. The data were collected by questionnaire and medical record, and then were analyzed by linear regression model.Results: Education ≥ Senior High School (b= 10.25; 95% CI=5.24 to 15.26; p<0.001) and family income ≥ Minimum Regional Wage (b= 0.47; 95% CI=0.12 to 0.83; p=0.009) increased quality of life in patients with cervical cancer. Age ≥ 45 years (b=-0.53; 95% CI=-0.84 to -0.21; p=0.001) decreased quality of life in patients with cervical cancer.Conclusion: The quality of life of patient with cervical cancer is determine by age, education, and family income. Key Words: age, social economic status, quality of life, cervical cancer, chemotherapyCorrespondence: Hidayah Nur Fadhilla. Masters Program in Public Health, Sebelas Maret University, Surakarta. Email: fadhillahidayah@student.uns.ac.id. Mobile: +6285729955373.Journal of Epidemiology and Public Health (2017), 2(1): 11-19https://doi.org/10.26911/jepublichealth.2017.02.01.02